PENAKSIR RASIO-CUM-DUAL UNTUK VARIANSI POPULASI PADA SAMPLING ACAK SEDERHANA - Siska Yuliati; Arisman Adnan; Haposan Sirait (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
This article discusses three estimators for estimating population variance in simple random sampling i.e. ratio estimator, dual ratio estimator and ratio cum dual estimator which is a review of the article of Yadav and Kadilar [Journal of Reliability and Statistical Studies, 6 (2013): 29-34]. These there estimators are all biased, and MSE (mean square error) of each estimator can be obtained. Furthermore, these MSE are compared to each other. An example is given to show the efficiencies of estimators.